Genital lymphoedema due to anogenital granulomatosis. (February 2013) - Gordon, K D; Brice, G; Walker, Y; Pollok, R; Mortimer, P; Slater, C
A 21-year-old man presented to genitourinary (GU) medicine physicians with (initially) painful penile and scrotal swelling. A diagnosis of anogenital granulomatosis was confirmed on histological analysis of penile skin. Enquiring about systemic symptoms resulted in the additional diagnosis of gastrointestinal Crohn's disease. The patient is now receiving immunosuppressive therapy to treat both conditions.